Prognostic value of baseline plasma D-dimer levels in sepsis: a prospective cohort study - Xiaoxiao Qu; Shishi Wang; Xuanmei Ye; Guosong Jiang; Mihereguli Kuerban; Qipeng Xie (Practical Laboratory Medicine)
Background: Plasma D-dimer, a fibrin degradation product, reflects coagulation activation and is often elevated in critically ill patients. Its prognostic significance in sepsis, particularly for short-term outcomes, remains unclear. Methods: In this prospective cohort study, we enrolled 175 adult ICU patients with sepsis (Sepsis-3 criteria) from March 2024 to February 2025. Plasma D-dimer levels were measured at ICU admission and daily for five days. D-dimer levels were categorized into quartiles. The primary outcome was 30-day all-cause mortality; secondary outcome was in-hospital septic shock. Associations were analyzed using Cox regression, Kaplan–Meier analysis, and subgroup analysis. Results: Elevated admission D-dimer levels were significantly associated with increased risks of 30-day mortality and septic shock. Each 1 μg/mL increase in D-dimer was linked to a 6 % higher mortality risk (HR = 1.06; 95 % CI: 1.02–1.11; P = 0.008) and an 8 % higher septic shock risk (HR = 1.08; 95 % CI: 1.03–1.12; P < 0.001), after adjusting for confounders. Patients in the highest quartile had the worst outcomes. A significant interaction with serum amyloid A (SAA) was observed for mortality (P = 0.043), but not for septic shock. Conclusion: Baseline plasma D-dimer levels independently predict 30-day mortality and septic shock in sepsis. D-dimer may serve as a valuable early biomarker for risk stratification in sepsis management.